Expansive high-performance concrete for chemical-prestress applications. (May 2018) - Wyrzykowski, Mateusz; Terrasi, Giovanni; Lura, Pietro
Abstract: By inducing a large expansion in concrete at early age, chemical-prestressing of reinforcement can be achieved. Expansions sufficient to achieve this purpose are normally obtained with a combination of admixtures (or expansive cement) and special curing methods. However, these special concrete mixtures may suffer from excessive expansion and the resulting loss of mechanical properties and durability. In this work, a combination of expansion-promoting (based on calcium sulfoaluminate, CSA) and shrinkage reducing additives (superabsorbent polymers, SAP and shrinkage-reducing admixture, SRA) is applied to produce concrete with outstanding mechanical properties and good durability. After initial underwater curing until 28 d and further drying at 70%RH, a residual expansion in unrestrained conditions of about 4000 μm/m was obtained, which enables reaching a central concrete prestress of about 2.5–3 MPa. In spite of the high residual expansion, compressive strength of about 100 MPa was obtained and the concrete had very high freeze-thaw resistance.